2015
DOI: 10.1001/jamapsychiatry.2015.1154
|View full text |Cite
|
Sign up to set email alerts
|

Telephone-Delivered Cognitive Behavioral Therapy and Telephone-Delivered Nondirective Supportive Therapy for Rural Older Adults With Generalized Anxiety Disorder

Abstract: IMPORTANCE Generalized anxiety disorder (GAD) is common in older adults; however, access to treatment may be limited, particularly in rural areas.OBJECTIVE To examine the effects of telephone-delivered cognitive behavioral therapy (CBT) compared with telephone-delivered nondirective supportive therapy (NST) in rural older adults with GAD. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial in the participants' homes of 141 adults aged 60 years and older with a principal or coprincipal diagnosis of GAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 47 publications
3
103
1
3
Order By: Relevance
“…13 The current findings demonstrate the superiority of CBT-T on reducing worry and general anxiety symptoms measured 12 months after the cessation of the intervention. The effect on depressive symptoms was borderline (p = 0.0376 versus a critical value of 0.0375) and the effect was not maintained on GAD symptoms, which was somewhat reduced (p = 0.088) by the 1-year follow-up assessment.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…13 The current findings demonstrate the superiority of CBT-T on reducing worry and general anxiety symptoms measured 12 months after the cessation of the intervention. The effect on depressive symptoms was borderline (p = 0.0376 versus a critical value of 0.0375) and the effect was not maintained on GAD symptoms, which was somewhat reduced (p = 0.088) by the 1-year follow-up assessment.…”
Section: Discussionsupporting
confidence: 55%
“…We demonstrated the superiority of CBT-T for reducing worry, GAD symptoms, and depressive symptoms 13 immediately upon completing treatment. The purpose of the current study is to determine if intervention effects were still present 1 year after completing treatment.…”
mentioning
confidence: 81%
“…Other clinical studies that have used remote approaches to evaluate therapeutics have demonstrated the feasibility of such an approach. [38][39][40][41][42][43] That said, contacting many individuals was difficult because of telephone blocking services, absence of a prior relationship, and incomplete information provided. The inclusion of data checks to identify any missing responses would likely have reduced inadvertent omissions in sometimes lengthy forms and surveys.…”
Section: Discussionmentioning
confidence: 99%
“…18,[36][37][38][39][56][57][58][59][60][61][62][63][64] The total sample for the meta-analysis was N = 985 with an average age of 68.16 years (SD = 2.52).…”
Section: Study Selectionmentioning
confidence: 99%